(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
In the result of detailed three-dimensional lithogeochemical sampling of the Sungun Cu–Mo deposit (NW Iran) new geochemical method is developed for the study of the metasomatic alteration zones based on the application for exploration of such zones the contrast primary halos of the macroelements. The contrast vertical geochemical zonality revealed in the structure of these macroelements’ halos is recommended as a criterion for assessing of the erosion level of the lithogeochemical halos and metasomatic alteration zones in bedrock within the covered areas, where the ore-bearing bedrock is covered by overburden and can not be sampled without mining and drilling works.